2022
DOI: 10.1111/jdv.18635
|View full text |Cite
|
Sign up to set email alerts
|

Patient presentation, skin biopsy utilization and cutaneous malignant melanoma incidence and mortality in northern Italy: Trends and correlations

Abstract: Background The global increase in incidence of cutaneous malignant melanoma (CMM) occurring in the past decades has been partly attributed to increased diagnostic scrutiny of early lesions, with a potential phenomenon of overdiagnosis. The reported positive linear relation between skin biopsy rate and incidence of early CMM is compatible with this hypothesis. Objectives We explored the ecological association between the trends in annual dermatologic office visit rates, skin biopsy rates, incidence rates of in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…It has also been suggested that the potential increase in morbidity and costs associated with overdiagnosis of thin lesions due to regular DSE, could be outweighed by the reduction in melanoma burden, given a genuine increase in the incidence of melanoma (4), such as reported in our district (5).…”
Section: Discussionmentioning
confidence: 68%
“…It has also been suggested that the potential increase in morbidity and costs associated with overdiagnosis of thin lesions due to regular DSE, could be outweighed by the reduction in melanoma burden, given a genuine increase in the incidence of melanoma (4), such as reported in our district (5).…”
Section: Discussionmentioning
confidence: 68%
“…[5][6][7][8] Furthermore recent Italian data using a population cancer registries have suggested an overload primary care physician referral for a suspicious lesions for an increased patient presentation at dermatologic offices and have recommended a better GP triage in the referral patients. 11 A recent review has been highlighted the importance and the effects of educational course on skin cancer detections.…”
Section: Discussionmentioning
confidence: 99%
“…The Emilia-Romagna Region and the Sicily Region were selected for the study for two reasons: first, their different latitude and, second, the fact that the local investigators had access to the Regional outpatient care files, which contain the individual electronic records of services delivered in outpatient clinics of public health facilities. Among the cancer registries participating in the research project, 3,[14][15][16] four (Parma, Modena, Ferrara and Romagna) out of five in the Emilia-Romagna Region and three (Catania-Messina-Enna, Siracusa and Ragusa) out of four in the Sicily Region (Online Supplementary Figure S1) met the following eligibility criteria : (1) having CMM incidence and mortality data for ⩾10 consecutive years; (2) having incidence data both for in situ and invasive CMM; and (3), with respect to the latter, being able to provide tumour thickness information for at least 75% of CMM cases on an annual basis. On 1 January 2023, people living in their registration areas totalled 2,606,465 in the Emilia-Romagna Region and 2,775,019 in the Sicily Region.…”
Section: Sources Of Datamentioning
confidence: 99%
“…The results published so far allow new insights into the promising results of national efforts for the control of the disease. 3,[14][15][16] As a part of this project, we have carried out a study with the primary objective of comparing the time trends in overall and Breslow tumour thickness-specific incidence rates, CMM mortality rate, dermatologic office visit rate and skin biopsy rate between the Emilia-Romagna Region (northern Italy) and the Sicily Region (southern Italy). We used the 'number needed to screen' for a diagnosis of CMM and the five-year net survival (NS) rate as secondary end points.…”
Section: Introductionmentioning
confidence: 99%